2019
DOI: 10.1080/14767058.2019.1677597
|View full text |Cite
|
Sign up to set email alerts
|

The effect of race and supplementation on maternal and umbilical cord plasma folates

Abstract: Objective: The purpose of this study is to test the hypothesis that race and supplementation affect the concentration and correlation of various folate species in maternal and umbilical cord blood. Methods: This is a single-center, prospective, cross-sectional cohort of cord blood samples obtained from 40 uncomplicated term pregnancies as a pilot study, following a protocol approved by the Institutional Review Board. High performance liquid chromatography mass spectrometry quantitated the following concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Supplementation with folic acid had less of an effect on maternal and cord blood sample folates for African Americans. 52 A study of women living in Georgia found that ∼25% of women were taking a folic acid supplement preconception, with non-Hispanic women twice as likely as Hispanic women to take folic acid supplements. 53 In terms of differences in metabolism, among women taking folic acid supplements, the largest increase in folate levels was noted in White women, followed by Hispanic women, with Black women experiencing the lowest serum folate levels.…”
Section: Folic Acidmentioning
confidence: 99%
“…Supplementation with folic acid had less of an effect on maternal and cord blood sample folates for African Americans. 52 A study of women living in Georgia found that ∼25% of women were taking a folic acid supplement preconception, with non-Hispanic women twice as likely as Hispanic women to take folic acid supplements. 53 In terms of differences in metabolism, among women taking folic acid supplements, the largest increase in folate levels was noted in White women, followed by Hispanic women, with Black women experiencing the lowest serum folate levels.…”
Section: Folic Acidmentioning
confidence: 99%